Impacto de diferentes colonizações bacterianas sobre o estado nutricional, função pulmonar e gravidade clínica em pacientes com fibrose cística - Valadão, Maria Clara da Silva (2017)
Introduction: Cystic fibrosis is an autosomal recessive genetic disorder characterized mainly by obstruction and inflammation of the airways leading to the chronic establishment of microorganisms. Acute infections (exacerbations) and/or chronic colonization lead to a progressive decline in lung function that leads to respiratory failure, the main cause of death among these individuals. Despite advances in survival, aspects related to infections still need to be reviewed. Thus, the main objective of the study was to evaluate the impact of different bacterial colonizations on nutritional status, lung function and clinical severity in patients with cystic fibrosis (CF). Methods: This is a retrospective cohort study that included patients with a confirmed diagnosis of CF, aged > 3 years and presenting complete data in a reference database of cystic fibrosis and / or available medical records. Anthropometric information (weight and height for the purpose of calculating BMI) and nutritional status, clinical severity data, colonization of airway secretions in addition to lung function (FEV1, FVC and FEV1/FVC). All the data collected were the annual evaluation of these subjects, between the period from 2009 to 2013. For statistical purposes, the Friedman test (Dunn's post-test) and the Mann Whitney U test were used. Results: We included 68 patients with CF out of a total of 80 who are regularly followed by the service, with 57.4% being male with a mean age of 10.35 years at baseline. During the five-year follow-up (mean of 3.55 years), nutritional status (p = 0.743) and clinical severity score (p = 0.235) remained stable. There was a statistically significant reduction of FEV1/FVC ratio over the follow-up (from year 2 to year 3 and year 2 to year 5; p <0.05). The most frequent colonizations were oxacillin-sensitive Staphylococcus aureus (MSSA) (29.8-46.3%), followed by non-mucoid Pseudomonas aeruginosa (PA) (8.5-19.4%), Burkholderia Cepacia Complex CBC) (4.9-21.3%), mucoid PA (2,4-6,5 %) and oxacilina/meticilin-resistent Staphylococcus aureus (MRSA) (2,4- 16,1%). Patients who were colonized throughout the study by MRSA (p = 0.040) had a reduction in FEV1 (p = 0.004) and FVC (p = 0.005) in year 5 compared to those not colonized by this bacteria. In addition, individuals with non-mucoid BP had a reduction (p = 0.007) in FVC. Conclusions: Our findings demonstrate that bacterial colonization by oxacilina/meticilin-resistent Staphylococcus aureus and non-mucoid Pseudomonas aeruginosa is related to worsening lung function (FEV1 and FVC). However, the impact of the different colonizations on BMI and on the clinical severity of Shwachman-Kulczycki score over the 5 years was not observed. Key words: Microbiology, nutritional status, respiratory function tests, prognosis, cystic fibrosis.